Kearifan Lokal dalam Hikayat Komering Pitu Phuyang - Dedi Febriyanto; Kiki Nurjana; Eka Anista; Dedi Mardiansyah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
The purpose of this study is to explore and describe local wisdom in the Hikayat Komering Pitu Phuyang. The study used a qualitative descriptive method with a sociological literature approach. Source of research data is Hikayat Komering Pitu Phuyang by Himawan Bastari. The data were collected using the reading-note technique, while the content analysis technique carried out the data analysis. The results showed that the Hikayat Komering Pitu Phuyang contains very diverse local wisdom. Local wisdom includes (1) Wangsa Buay Tumi's belief in tambo as a means of information that is believed to be true, (2) the belief system in Belaksa Kepampang and Ikahua as the embodiment of gods, (3) the tradition of giving adok as a form of appreciation, (4) ) the government system in the form of a kingdom, (5) the tradition of slaughtering virgins and virgins as evidence of worship of gods, (6) the caste tradition in royal family marriages as a symbol of honour, (7) the tradition of asceticism at the top of a mountain as a means of approaching oneself to the God, (8) society that has the principles of religious life, full responsibility, and hard work, (9) a residential system that reflects the breadth of the way the people think.